МАКРОФІНАНСОВА ВІДПОВІДАЛЬНІСТЬ ЦЕНТРОБАНКІВ: ТЕОРЕТИЧНІ ЗАСАДИ Й ІНСТИТУЦІОНАЛЬНІ ДИЛЕМИ - Козюк, Віктор Валерійович (Науковий журнал «Світ фінансів», 2018)
Козюк В. В. Макрофінансова відповідальність центробанків: теоретичні засади та інституціональні дилеми. Посткризова тенденція до посилення макрофінансової відповідальності центробанків має бути пов’язана не стільки з активістським управлінням попитом, скільки з переглядом погляду на зв’язки між реальним і фінансовим сектором. Відмінності в баченні взаємодії цінової та фінансової стабільності і, відповідно, інституціональної модальності їх забезпечення ускладнюють пошук оптимального інституціонального дизайну центробанку з розширеною зоною відповідальності. Доведено, що підвищення відповідальності за фінансову стабільність має відбуватися на основі збереження пріоритетності мандата цінової стабільності, підвищення рівня незалежності центробанку та координації між монетарною і макропруденційною політикою. Показано, що вразливість макрофінансової відповідальності до політичного тиску тільки підвищується. Козюк В. В. Макрофинансовая ответственность центробанков: теоретические основы и институциональные дилеммы. Посткризисная тенденция к усилению макрофинансовой ответственности центробанков должна связываться не столько с активистским управлением спросом, сколько с просмотром взгляда на связи между реальным и финансовым сектором. Различия в видении взаимодействия ценовой и финансовой стабильности и, соответственно, институциональной модальности их обеспечения затрудняют поиск оптимального институционального дизайна центробанка с расширенной зоной ответственности. Доказано, что повышение ответственности за финансовую стабильность должна происходить на основе сохранения приоритетности мандата ценовой стабильности, повышения уровня независимости центробанка и координации между монетарной и макропруденциальных политикой. Показано, что уязвимость макрофинансовой ответственности к политическому давлению только повышается. Koziuk V. Macrofinancial responsibility of central banks: theoretical foundation and institutional dilemmas. Introduction. Prediction that price stability as well as inflation targeting in commodity rich countries is very fragile typically based on logical relation between commodity prices fluctuations and macroeconomic instability. But in the same time, while counter-cyclical instruments appear, commodity prices shock should be taken as supply shock. Thus, inflation instability in resource rich countries should be taken as consequences of macroeconomic mismanagement. Purpose. The purpose of the paper is to validate rejection of fatalism in negative influence of resource richness on price stability. Also it is important to show that inflation targeting regime compatible with large commodities export. In the same time it is necessary to take into account political regime as a supporting factor of adoption that regime of macroeconomic policy that is consistent with price stability. Results. It is proved empirically that commodity abundance per se is not in conflict with price stability. We rich such conclusions basing on simple multifactor regression model that combine macroeconomic policy regime dummies (maturity of inflation targeting, sovereign wealth fund in operation, central bank independence, exchange rate regime) and structural features of the resource rich economies like commodity export, economic complexity, financial depth, democracy. On example of 68 resource rich countries it is shown that price stability parameters (mean inflation, 1999-2017 and standard deviation of it) are not in undoubtfull relation with fraction of nonmerchandise export, but they are in opposite relation with inflation targeting and sovereign wealth funds dummies. Resource endowed countries are not homogenous from political regime point of you. Such regime is important driver of macroeconomic policy choice. Advanced democracies are likely to choose inflation targeting, flexible exchange rate and central bank independence, while wealthy autarkies are likely to prefer fixed exchange rates and sovereign wealth funds. It is mean that price stability is not just vulnerable to commodity factor but is to unstable political regime under which it is hard to implement counter-cyclical regime of macroeconomic policy. Conclusions. Commodity wealth is not precondition to price instability. But political regime is important activate that type of macroeconomic policy regime that consistent with low and stable inflation. By the structural features Ukraine is closer to democracies with mean level of economic complexity and financial depth. Due this inflation targeting regime is more appropriate meaning priority of price stability and exchange rate flexibility.